Empowerment Partnership Public Group Business in Tebet District, South Jakarta City - Dewi Wuisan; Napitupulu, Joshua Fernando; Herlina Lusmeida (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
The potential of cassava as a staple food in Indonesia, although not fully utilised. Innovation in processing cassava into chips is a solution to increase cassava consumption and overcome nutritional problems such as stunting. Through the "Keripik Bangjo" brand, consumers can enjoy practical cassava chips rich in nutritional benefits. However, the company faces several internal problems, including a lack of space production, Which is inadequate, limitations on the Power man, And the need for funds for business expansion. Solutions and output targets to overcome the problems faced by the company. Solutions include providing funds to improve production sites, involving mothers as partners in production, and expanding marketing to international, national, and local markets. Output targets include increasing sales, product development, intellectual property management, and growing income for business partners. The implementation method focuses on improving business partners' skills and capacity, especially moms involved in the production of chips Bang Jo. This involved counselling, surveys, and training in making Bangjo chips. Through this activity, consumer interest in the product will increase, sales will increase, and there will be open opportunities to cooperate with partners for new distribution.